Strengthening of Islamic Quality Management Practices Through Culture of Perfection (ITQAAN) and the Value of Courtesy (IHSAN) Toward The Business Performance of Muslim Entrepreneur - Saiful Bahri, Mohamed; W.A., Wan Ab Aziz; Ibrahim, M.S. Muda (2014)
Islamic quality management practices are important processesin the running and the management of a company that focuses on products or provides services in line with the needs and demands of Sharia. These practices, if properly managed, will achieve success and excellence not only in the real world but also in the hereafter. Quality management system pioneered in the West, such as Total Quality Management, emphasizes the technical aspects like input-output, procedures and work processes, customer preferences, and relationships with suppliers. They ignored spiritual aspects such as welfare of workers, the value of goodwill, integrity, ethics, morality and social responsibility. Thus, an owner or manager must establish a quality management system based on Islamic values that emphasizes culture of perfection (itqan) and values of courtesy (ihsan). The two main pillars are to ensure continuity and smooth running of the quality management system in an enterprise. They also make the quality management system more humane and closer to the heart of every member of the organization. Accordingly, this study will view the two concepts as moderating factors, and will examine their impact on the quality of management practices of muslimentrepreneurs, bye valuating their business performances. Thereafter, we can proposestreng thening measures for effective quality management system according to Islamic values. The findings confirmed that both the factors showed significant effect in the relationship between quality management practices and business performances ofmuslim entrepreneurs. The emphasis on the culture of perfection (itqan)and the value of courtesy (ihsan)contributes to a more holistic quality management system.